2010
DOI: 10.2478/s11536-009-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive options in severe cases of Hidradenitis suppurativa

Abstract: AbstractHidradenitis suppurativa is a chronic, debilitating inflammatory disease of apocrine glands characterized with abscesses and nodular lesions. The treatment of Hidradenitis suppurativa consists of topical antibacterial or antiseptic solutions, systemic antibiotics, steroids, hormonal therapy, anti-tumor necrosis factor, and various surgical procedures. In this report, we present a series of 14 cases with severe Hidradenitis suppurativa. Surgical options are reviewed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Soldin et al [ 13 ], concluded that different flaps can be used depending on size of the excised defect, recommending a fasciocutaneous flap for small to medium defects and pedicled parascapular flaps for larger defects. It is reasonable to conclude that most studies agree that flap reconstruction is superior to direct closure, STSG, and healing by secondary intention [ 8 9 15 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soldin et al [ 13 ], concluded that different flaps can be used depending on size of the excised defect, recommending a fasciocutaneous flap for small to medium defects and pedicled parascapular flaps for larger defects. It is reasonable to conclude that most studies agree that flap reconstruction is superior to direct closure, STSG, and healing by secondary intention [ 8 9 15 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Axillary HS is bilateral in 75% of cases [ 7 ]. The exact aetiology of HS still remains unclear; however, possible cited associations include cigarette smoking, obesity, diabetes mellitus, and Crohn's disease [ 8 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contracture development and limitation of movement frequently seen in secondary healing, primary suture, and wound closure with graft suture are observed less frequently in flap repair method. Especially in axillary, perineal, and perianal sites, repair with fasciocutaneous or musculocutaneous flap is recommended 22,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Especially in axillary, perineal, and perianal sites, repair with fasciocutaneous or musculocutaneous flap is recommended. 22,29,30 Wound complications such as infection and dehiscence are seen frequently in perianal, perineal, and buttocks disease. In the presence of prevalent and acute disease in these sites, colostomy may help control of infection and contribute to the success of radical surgical treatment methods.…”
Section: Discussionmentioning
confidence: 99%